2008
DOI: 10.1021/bm800565u
|View full text |Cite
|
Sign up to set email alerts
|

Combining Electrospun Scaffolds with Electrosprayed Hydrogels Leads to Three-Dimensional Cellularization of Hybrid Constructs

Abstract: A common problem in the design of tissue engineered scaffolds using electrospun scaffolds is the poor cellular infiltration into the structure. To tackle this issue, three approaches to scaffold design using electrospinning were investigated: selective leaching of a water-soluble fiber phase (poly ethylene oxide (PEO) or gelatin), the use of micron-sized fibers as the scaffold, and a combination of micron-sized fibers with codeposition of a hyaluronic acid-derivative hydrogel, Heprasil. These designs were achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
170
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(173 citation statements)
references
References 27 publications
2
170
1
Order By: Relevance
“…3D tissues are being formed with spun nanofibers incorporated into composite designs [48,[54][55][56][57], and hydrogel 3D composites with stitched fibers have been tested in animal models [54,55]. Thus, as biomimetic studies reduce the amount of cytotoxic crosslinkers and solvents used in electrospun scaffolds, continued efforts to improve biocompatibility may increase the frequency and efficacy of electrospun scaffold use in clinical trials for whole-organ engineering applications.…”
Section: Electrospun Nanofibersmentioning
confidence: 99%
“…3D tissues are being formed with spun nanofibers incorporated into composite designs [48,[54][55][56][57], and hydrogel 3D composites with stitched fibers have been tested in animal models [54,55]. Thus, as biomimetic studies reduce the amount of cytotoxic crosslinkers and solvents used in electrospun scaffolds, continued efforts to improve biocompatibility may increase the frequency and efficacy of electrospun scaffold use in clinical trials for whole-organ engineering applications.…”
Section: Electrospun Nanofibersmentioning
confidence: 99%
“…For instance, Ekaputra et al incorporated biodegradable hyaluronic acid hydrogel into electrospun microfibers through simultaneous electrospraying and showed that this approach allowed for significant improvements in cell infiltration. 39 The approach was also claimed to be beneficial as it potentially allows controlled release of growth factors by utilizing the hydrogel as a release vehicle. In another approach, Pham et al demonstrated a multilayered combination of micro-and nanofibers to generate scaffolds that exploited the resulting large pores from using microfibers to permit cell vertical penetration in combination with the physical mimicry of ECM through the nanofibers.…”
Section: Defining Fiber Patterns and Topographymentioning
confidence: 99%
“…37 Several different techniques that can facilitate larger pore size and cellular invasion into the fibrous meshes have been proposed, such as combining microfibers with electrospun nanofibers 38 or the use of a gel as a second phase between. 39 However, in parallel to these efforts, extensive attention is still directed towards understanding the influence of physical, chemical and topographical features of various electrospun fibers on cell attachment, 40,41 morphology, 42 proliferation, 43 differentiation, 44,45 and migration. 46,47 Thin fiber mats, being on average one to a few fiber layers thick, form more of a two-dimensional surface that provides the same chemical and topographical features of individual fibers and their orientation as in three-dimensional matrices, but at the same time allows the traditional investigation of cell attachment, spreading and migration on flat substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Another method involves co-electrospinning the polymer of choice with a different, water-soluble, polymer which is later dissolved out of the template [25]. However, when these sacrificial fibers are removed, the fibers around them tend to shift, and eventually collapse the newly formed pores [26,27]. In addition to the work in modifying the electrospinning process, other groups have tried changing the collecting plate in order to alter the density of the resulting template.…”
Section: Introductionmentioning
confidence: 99%